Adalimumab: Another Medication Related to Osteonecrosis of the Jaws?. (21st March 2016) - Cassoni, Andrea; Romeo, Umberto; Terenzi, Valentina; Della Monaca, Marco; Rajabtork Zadeh, Oriana; Raponi, Ingrid; Fadda, Maria Teresa; Polimeni, Antonella; Valentini, Valentino
Abstract : Objective. The acronym MRONJ has been created in order to identify "Medication-Related Osteonecrosis of the Jaw, " observed after the use of Bisphosphonates, RANK ligand inhibitor, and antiangiogenic medications. Only a case of osteonecrosis of the jaw in a Chron's disease patient following a course of Bisphosphonate and Adalimumab therapy has been recently described, so that it has been supposed that also this medication could promote manifestation of osteonecrosis. Clinical Case . On August, 2014, a 63-year-old female with a history of idiopathic arthritis treated with medical treatment with Adalimumab from 2010 to 2013 presented referring pain in the right mandible. Results . This patient presented with nonexposed osteonecrosis of the jaw after placement, on September, 2010, of four titanium fixtures in the mandible. Conclusions . The authors suggest that the biologic therapy with an anti-TNF- α antibody might promote the manifestation of osteonecrosis and compromise oral healing capacity of the bone.